Treatment of surfactant-laden wastewater in horizontal subsurface flow constructed wetlands using Phragmites SPP - Mulingbayan, Mark Tom Q (2005)
The removal of chemical oxygen demand (COD) and anionic surfactants (as linear alkybenzene sulfonates, or LAS) from commercial laundry wastewater in horizontal subsurface flow constructed treatment wetlands using phytoremediation-related pollutant removal mechanisms was investigated in two pilot-scale reed beds planted with two species of the common reed, Phragmites australis and Phragmites karka, in four experimental runs at varying hydraulic gradients and theoretical hydraulic retention times (HRT). The COD and anionic surfactant removal efficiencies of the Phragmites karka bed ranged from 76.8 to 58.6 percent, and 90.1 to 91.9 percent, respectively, slightly better than the removal efficiency of the Phragmites australis bed with observed values of 74.8 to 81.82 percent for COD and 86.6 to 90.9 percent for surfactants. Theoretical HRT's ranged between 2 to 4 days. The surfactant removal rate for both beds did not vary greatly within the mentioned range of HRT, although the removal performance of Phragmites australis was less stable. In one run, a fluorescent dye tracer test using Rhodamine WT as the dye tracer was carried out in both reed beds to compare the theoretical and actual HRT's. The actual HRT's in both beds were found to be shorter than the calculated theoretical hydraulic retention time, due to clogging of the inlet and surface tracking as suspended solids and sludge had accumulated in the inlet zones. IT was also observed that the actual HRT of P. australis bed was shorted by one day compared to that of the P. karka bed, for the same theoretical HRT.